Design and construction of an instrument to evaluate the potential of employees management skills - Arana Mayorca, Walter Hugo (2021)
The purpose of this article was the design and construction of an instrument (test) to evaluate the potential of workers’ managerial skills, considering the dimensions: development of self-knowledge, stress management and well-being, creative problem solving, management of conflict, worker motivation, supportive communication, gaining power and influence, building effective teams, leading positive change, and empowerment and delegation. The research is instrumental, with a quantitative approach, a non-experimental cross-sectional design and a descriptive level. The 50 items of the instrument under construction were subjected to Expert Judgment and the average value of the Aiken Coefficient V = 0.962 was obtained, which indicates high content validity. In the Item correlation - Total correlation of corrected items, values between 0.40 and 0.69 were obtained, meaning that the test has internal validity. Reliability was evaluated using the internal consistency coefficient method, applying the test to a sample of 1874 workers from 61 companies in Metropolitan Lima, whose Cronbach’s Alpha Coefficient was 0.967, which denotes a very strong reliability. Likewise, the scale was prepared using the percentile of the dimensions. In conclusion, the construction of the Test Potential Management Skills was satisfactorily completed because the results were highly valid and reliable.